Multi-criteria land use suitability analysis for livestock development planning in Hangzhou metropolitan area, China. (10th September 2017) - Qiu, Lefeng; Zhu, Jinxia; Pan, Yi; Hu, Wei; Amable, Gabriel S.
Abstract: Land suitability analysis is an important step in land use planning for livestock development because of its high efficiency to allocate livestock farms to the most suitable land areas and minimize adverse effects on environment. This study aimed to use two multi-criteria analysis approaches: Weighted Linear Combination (WLC) and Ordered Weighted Averaging (OWA), to comparatively evaluate and map land use suitability for livestock production in Hangzhou metropolitan area, China. The evaluation used eight factors as suitability criteria, relating to topographic, environmental, human factors, and socio-economic data. The analytic hierarchy process (AHP) method and GIS techniques were integrated into the evaluation models to create the land suitability map. The results of WLC approach showed that 11.4% of the total area was highly suitable for livestock production while 48.6% was unsuitable. Of these, areas located far from central city had higher suitability, while areas close to the urban district, drinking water source area, ecological and natural conservation area, had lower suitability. Sensitivity analysis indicated this expert suitability results for livestock production were robust. Indirect validations conducted by mutual comparisons of suitability maps computed using the WLC and OWA approaches demonstrated 90.4% of the overall agreement with a kappa coefficient of 0.857, indicating that both methods provide very similar spatial land use suitability distributions. Ecological fitness was evaluated by comparing the suitability analysis result with a previous livestock development planning and several recommendations aimed at improving the long-term livestock development plans were made for Hangzhou.